High-strength refractory ceramic material and method for producing the same
Patent Information
- Application Number
- CN202611308963.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-11-03
AI Technical Summary
Existing refractory ceramic materials cannot simultaneously achieve high suspension stability, excellent room temperature and high temperature mechanical properties, and thermal shock resistance in water-based suspension systems.
A mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure is generated in situ through high-temperature pre-sintering, and a nano-SiO2 active layer is coated on the powder surface with a silica sol liquid phase to form multiphase ceramic particles.
It improves the water-based suspension properties of refractory ceramic powder and enhances the room temperature and high temperature mechanical properties and thermal shock resistance of the shaped sintered body.
Smart Images

Figure CN123026437A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of refractory materials for casting, and more specifically, to a high-strength refractory ceramic material and its preparation method. Background Technology
[0002] Refractory ceramic materials are widely used in metallurgy, building materials, aerospace and other fields due to their excellent high-temperature stability, corrosion resistance and mechanical strength. As advanced manufacturing technologies place increasingly higher demands on the forming precision of ceramic materials, the water-based suspension stability of powders has become a key factor affecting the uniformity of green bodies and the performance of final products.
[0003] To improve the mechanical properties of sintered refractory ceramics, existing technologies often employ pre-sintering to form mullite and spinel reinforcing phases, or introduce ZrO2 for phase transformation toughening to enhance toughness. However, single or simply compounded reinforcing phases often fail to achieve comprehensive performance: for example, mullite is beneficial for high-temperature creep resistance but lacks sufficient strength at room temperature; spinel has a low coefficient of thermal expansion, which helps resist thermal shock but is difficult to form high-strength bonds; while the introduction of ZrO2 can improve toughness, it may adversely affect high-temperature stability. Furthermore, existing literature reports the use of sol-gel methods to coat SiO2 onto the powder surface to improve dispersibility, but this only involves surface coating without synergistic effects with the in-situ generated multiphase structure within the powder, making it difficult to simultaneously improve water-based suspension performance, room-temperature and high-temperature mechanical properties, and thermal shock resistance.
[0004] Therefore, there is an urgent need for a refractory ceramic powder and its preparation method that can achieve high suspension stability in water-based systems and enable the sintered body to possess excellent mechanical properties at room temperature and high temperature as well as thermal shock resistance. Summary of the Invention
[0005] This invention provides a high-strength refractory ceramic material and its preparation method. It involves in-situ generation of a mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure through high-temperature pre-sintering, combined with a silica sol liquid phase coating on the powder surface to form a nano-SiO2 active layer. Utilizing the synergistic effect of these two methods, the water-based suspension stability of the powder is improved, as well as the room-temperature and high-temperature mechanical properties and thermal shock resistance of the sintered body are enhanced, thereby solving the problems mentioned in the background art. The existing technology for refractory ceramic materials has the problem of not being able to simultaneously achieve excellent water-based suspension stability, normal / high temperature mechanical properties of sintered bodies, and thermal shock resistance.
[0006] To achieve the above objectives, this invention provides a high-strength refractory ceramic material and its preparation method. The high-strength refractory ceramic material is a multiphase ceramic powder, comprising multiphase ceramic particles and a nano-silica active layer coating the surface of the multiphase ceramic particles. The multiphase ceramic particles contain mullite phase, magnesium aluminum spinel phase, and yttrium-stabilized zirconia phase, and are prepared from the following raw materials through high-temperature pre-sintering in-situ reaction, by mass: The industrial α-alumina powder contains 68-75 parts, with an Al2O3 content ≥99% and a median particle size D50 of 3μm. 15-25 parts of high-purity silicon micro powder, with SiO2 content ≥98% and median particle size D50 of 1μm; 2-6 parts of lightly calcined magnesium oxide powder, the MgO content of the lightly calcined magnesium oxide powder is ≥95%, and the median particle size D50 is 5μm; 2-6 parts of 3Y-Yttrium stabilized zirconia powder, which is ZrO2 powder containing 3 mol% Y2O3 and a median particle size D50 of 80 nm; Aluminum fluoride is added; the aluminum fluoride is chemically pure, and its dosage is 0.5% to 2.0% of the total mass of industrial α-alumina powder, high-purity silica powder, lightly calcined magnesia powder, and 3Y-yttrium stabilized zirconium oxide powder. The nano-silica active layer is formed by coating the surface of the composite ceramic particles with neutral silica sol, which accounts for 4% of the total mass of the composite ceramic particles, and then drying it. The SiO2 content in the neutral silica sol is 30%.
[0007] In the above technical solution, industrial α-alumina powder is used as the main phase raw material. Its high purity and moderate particle size ensure sufficient in-situ solid-phase reaction with silica powder and magnesium oxide, while preventing agglomeration due to excessive powder fineness, thus promoting the formation of a uniform and dense multiphase structure. High-purity silica powder, with a particle size of 1 μm, possesses high specific surface area and high reactivity. Under high-temperature conditions, it reacts with alumina in situ to form a mullite phase, which imparts excellent high-temperature strength and creep resistance to the material. Lightly calcined magnesium oxide powder, due to its light calcination treatment, exhibits high chemical activity, reacting in situ with excess alumina. Magnesium aluminum spinel phase is generated, which can improve the material's thermal shock resistance and slag erosion resistance. 3Y-yttrium stabilized zirconia powder is uniformly dispersed at the nanoscale. The introduction of Y2O3 allows ZrO2 to maintain a tetragonal phase structure at room temperature. When the material is subjected to external force, the tetragonal phase undergoes a stress-induced phase transformation to the monoclinic phase, absorbing energy with volume expansion. At the same time, microcracks are generated, which play a toughening role, thereby improving the fracture toughness and strength of the material. Furthermore, the nano-zirconia particles can be pinned at the mullite and spinel grain boundaries, inhibiting grain growth and further refining the microstructure.
[0008] Aluminum fluoride, acting as a mineralizer and sintering aid, undergoes gas-phase mass transfer or forms an intermediate phase with oxides in the system at high temperatures. This promotes ion migration between Al2O3, SiO2, and MgO, lowers the in-situ reaction temperature of mullite and magnesium aluminum spinel, and accelerates densification with the help of a small amount of liquid phase. The dosage of aluminum fluoride is controlled at 0.5% to 2.0% of the total mass of raw materials. If the dosage is too low, the mineralization effect is insufficient, the reaction is incomplete, and the porosity inside the particles is too high, leading to a decrease in strength. If the dosage is too high, the residual fluoride will corrode the ceramic grain boundaries and volatilize during high-temperature use, damaging the structural stability and refractory properties of the material. Through the above in-situ reaction, the mullite phase, magnesium aluminum spinel phase, and yttrium-stabilized zirconia phase intertwine and disperse within the particles, forming multiphase ceramic particles with strong interfacial bonding and synergistic microstructure.
[0009] Furthermore, a nano-silica active layer is formed by coating the surface of the obtained multiphase ceramic particles with neutral silica sol and drying it. The nano-silica active layer is formed by coating the surface of the multiphase ceramic particles with neutral silica sol containing 30% SiO2 and drying it. The coating amount is 4% of the total mass of the multiphase ceramic particles. This allows the particle surface to be uniformly covered with a continuous amorphous nano-silica film. The surface of this film is rich in silanol groups and has high chemical activity. On the one hand, it can act as an inorganic binder to promote bridging sintering between particles and between particles and the matrix at subsequent application temperatures, thereby improving the overall strength of the refractory product. On the other hand, it can improve the wettability and dispersibility of the multiphase ceramic powder in the aqueous system, avoid particle agglomeration, and facilitate subsequent molding and construction.
[0010] Further, by mass, the industrial α-alumina powder comprises 70 parts, the high-purity silicon micro powder comprises 25 parts, the light-burned magnesium oxide powder comprises 3 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 2 parts, and the amount of aluminum fluoride is 1.0% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
[0011] Furthermore, by weight, the industrial α-alumina powder comprises 75 parts, the high-purity silicon micro powder comprises 15 parts, the light-burned magnesium oxide powder comprises 6 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 4 parts, and the amount of aluminum fluoride is 0.5% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
[0012] Preferably, by weight, the industrial α-alumina powder comprises 68 parts, the high-purity silicon micro powder comprises 24 parts, the light-burned magnesium oxide powder comprises 2 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 6 parts, and the amount of aluminum fluoride is 2.0% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
[0013] On the other hand, the present invention also provides a method for preparing a high-strength refractory ceramic material, specifically including the following steps: S1. By mass, 68-75 parts of industrial α-alumina powder, 15-25 parts of high-purity silicon micro powder, 2-6 parts of lightly calcined magnesia powder, 2-6 parts of 3Y-yttrium stabilized zirconium oxide powder, and 0.5%-2.0% of aluminum fluoride by mass of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the lightly calcined magnesia powder, and the 3Y-yttrium stabilized zirconium oxide powder are mixed, and deionized water is added for wet ball milling to obtain a uniform slurry; S2. Spray granulation of the slurry to obtain spherical agglomerated particles; S3. The spherical agglomerated particles are pre-sintered at high temperature, so that alumina reacts in situ with high-purity silicon micro powder to form mullite phase, magnesium oxide reacts in situ with excess alumina to form magnesium aluminum spinel phase, and yttrium-stabilized zirconium oxide is dispersed in the grain boundaries and grain interiors of mullite and spinel to form a mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure. After cooling, the sintered mass is subjected to coarse crushing, medium crushing, pulverizing, and air classification in sequence to obtain multiphase ceramic particles. S4. The composite ceramic particles are mixed with 4% of the total mass of the composite ceramic particles in a neutral silica sol for liquid phase coating and dried to obtain a high-strength refractory ceramic material; the SiO2 content in the neutral silica sol is 30%.
[0014] In the above steps and methods, in step S1, the mass ratio of material, balls and water is controlled to be 1:2.5:0.8 during wet ball milling, the ball mill speed is 350 r / min, the ball milling is carried out for 4 hours, and the solid content of the resulting slurry is 55 wt%.
[0015] Preferably, in S2, the spray granulation uses a centrifugal spray drying tower with an inlet air temperature of 190°C, an outlet air temperature of 85°C, and an atomizing disc rotation speed of 12000 r / min, resulting in a median particle size D50 of 45 μm for the obtained spherical agglomerated particles.
[0016] More preferably, the pre-sintering process is as follows: heat to 1500°C at a heating rate of 5°C / min, hold at that temperature for 3 hours, and then cool naturally to room temperature.
[0017] Furthermore, in S4, the liquid phase coating is carried out in a high-speed mixer for 30 minutes; the drying is carried out at 105°C for 2 hours.
[0018] Furthermore, in S3, the coarse crushing uses a jaw crusher, the medium crushing uses a double roll crusher, the pulverizing uses an air jet mill, and the air jet classification uses an air jet classifier, resulting in a median particle size D50 of 20 μm for the obtained multiphase ceramic particles.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: The mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure is generated in situ by high-temperature pre-sintering, and a nano-SiO2 active layer is formed by coating the powder surface with silica sol liquid phase. The two work synergistically to improve the water-based suspension performance of the refractory ceramic powder, and at the same time improve the room temperature and high temperature mechanical properties and thermal shock resistance of the shaped sintered body. Attached Figure Description
[0020] Figure 1 This is a schematic diagram of the preparation method steps for the high-strength refractory ceramic material in this invention; Figure 2 This is a bar chart showing the 2-hour water-based suspension rate performance test results of each sample in this invention; Figure 3 This is a schematic diagram of the flexural strength at normal / high temperature for each sample in this invention; Figure 4 This is a bar chart showing the results of water-cooled thermal shock cycling at 1100℃ for each sample in this invention. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Existing refractory ceramic materials often fail to simultaneously achieve excellent water-based suspension stability, high-temperature / normal-temperature mechanical properties of the sintered body, and thermal shock resistance. This invention provides a high-strength refractory ceramic material and its preparation method. The high-strength refractory ceramic material is a multiphase ceramic powder, comprising multiphase ceramic particles and a nano-silica active layer coating the surface of the multiphase ceramic particles. The multiphase ceramic particles contain mullite phase, magnesium aluminum spinel phase, and yttrium-stabilized zirconia phase, and are prepared from the following raw materials through high-temperature pre-sintering in-situ reaction, by mass: 68-75 parts of industrial α-alumina powder; 15-25 parts of high-purity silicon micro powder; 2-6 parts of lightly calcined magnesium oxide powder; 2-6 parts of 3Y-yttrium stabilized zirconium oxide powder; Aluminum fluoride is added, and its dosage is 0.5% to 2.0% of the total mass of industrial α-alumina powder, high-purity silica powder, lightly calcined magnesia powder, and 3Y-yttrium stabilized zirconium powder; The nano-silica active layer is formed by coating the surface of the composite ceramic particles with neutral silica sol, which accounts for 4% of the total mass of the composite ceramic particles, and then drying it. The SiO2 content in the neutral silica sol is 30%.
[0023] Unless otherwise specified, all raw materials used in the following examples and comparative examples are commercially available industrial-grade products. Specifically, the industrial α-alumina powder has an Al2O3 content ≥99% and a median particle size D50 of 3 μm; the high-purity silica micropowder has an SiO2 content ≥98% and a D50 of 1 μm; the lightly calcined magnesia powder has an MgO content ≥95% and a D50 of 5 μm; the 3Y-yttrium stabilized zirconium oxide powder is ZrO2 powder containing 3 mol% Y2O3 and has a D50 of 80 nm; the aluminum fluoride is chemically pure; and the neutral silica sol has an SiO2 content of 30%. All of the above raw materials are commercially available.
[0024] Example 1:
[0025] This embodiment provides a high-strength refractory ceramic material, which comprises the following raw materials mixed in parts by weight: Industrial α-alumina powder: 70.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 3.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 2.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm.
[0026] In addition, add 1.0% of the total mass of the above raw materials as a mineralizing agent, aluminum fluoride, which is chemically pure.
[0027] In addition, this embodiment also provides a method for preparing the above-mentioned high-strength refractory ceramic material, such as... Figure 1 As shown, the specific steps include: The above raw materials were added to a wet ball mill along with deionized water, maintaining a material-to-ball-to-water mass ratio of 1:2.5:0.8. The ball mill speed was 350 r / min, and the mixture was milled for 4 hours to obtain a uniform slurry with a solid content of 55 wt%. The slurry was fed into a centrifugal spray drying tower for spray granulation. The inlet air temperature was 190℃, the outlet air temperature was 85℃, and the atomizing disc rotation speed was 12000r / min, resulting in spherical agglomerated particles with a median particle size D50 of 45μm.
[0028] The spray-granulated particles were placed in a high-temperature sintering furnace and heated to 1500℃ at a rate of 5℃ / min, held at that temperature for 3 hours, and then allowed to cool naturally to room temperature. During the sintering process, alumina reacted in situ with silica powder to form a mullite phase, and magnesium oxide reacted in situ with excess alumina to form a magnesium aluminum spinel phase. Yttrium-stabilized zirconium oxide was dispersed at the grain boundaries and within the grains of mullite and spinel, forming a mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure.
[0029] The sintered multiphase ceramic blocks are first coarsely crushed by a jaw crusher, then medium-crushed by a double-roll crusher, and finally pulverized into fine powder by an air jet mill. The powder is then classified by an air classifier to obtain multiphase ceramic powder with a median particle size D50 of 20 μm.
[0030] The graded multiphase ceramic powder was placed in a high-speed mixer, and 4% of the total mass of the powder was sprayed in with neutral silica sol. The silica sol contained 30% SiO2. The mixture was stirred for 30 minutes to coat the powder surface with silica sol, forming a nano-silica active layer. Then it was dried at 105℃ for 2 hours to obtain high-strength multiphase refractory ceramic powder.
[0031] XRD analysis showed that the main crystalline phase of the powder obtained in this embodiment was mullite, and it also contained characteristic diffraction peaks of magnesium aluminum spinel and yttrium-stabilized zirconia, confirming that the in-situ reaction during sintering successfully generated a mullite-magnesium aluminum spinel-zirconia multiphase structure. At the same time, the particle size distribution of the obtained powder was measured by a laser particle size analyzer, and its D50 was 20 μm.
[0032] Performance testing: Water-based suspension rate test: Weigh 10g of powder and place it in a 100mL stoppered graduated cylinder. Add 0.3g of silica sol (SiO2 content 30%), add deionized water to the 100mL mark, shake thoroughly, and let stand for 2 hours. Read the sedimentation layer volume V (mL). The suspension rate is calculated using the following formula: Suspension rate (%) = (1-V / 100) × 100%. The test showed that the 2-hour water-based suspension rate of the powder in this example was 95.5%.
[0033] Flexural strength test: The obtained powder was mixed with a 5% polyvinyl alcohol (PVA) solution at a mass ratio of 100:6. After thorough mixing, the mixture was placed in a mold and pressed into strips of 50 mm × 10 mm × 10 mm under a pressure of 10 MPa. After drying at room temperature for 24 hours, the strips were placed in a high-temperature furnace and heated to 1500℃ at a heating rate of 5℃ / min, held for 3 hours, and then cooled to room temperature with the furnace. The sintered specimens were placed on a universal testing machine, and the strength was determined using the three-point bending method with a span of 30 mm and a loading rate of 0.5 mm / min. The room temperature flexural strength was measured to be 15.2 MPa. Subsequently, the specimens were held at 1200℃ for 10 minutes in a high-temperature testing furnace, and the high-temperature flexural strength was measured under the same test conditions, with a result of 12.1 MPa.
[0034] Thermal shock resistance test: Sintered samples prepared under the same conditions were placed in a resistance furnace at 1100℃ and held for 10 minutes. They were then quickly removed and cooled in flowing water at 25℃ for 5 minutes. After removal, the samples were allowed to air dry, and the surface was inspected for visible cracks using the naked eye and a 5x magnifying glass. This cycle was repeated, and the number of cycles in which the first crack appeared was recorded. The test showed that after 15 cycles, no macroscopic cracks appeared on the sample surface, indicating excellent thermal shock resistance.
[0035] Example 2:
[0036] This embodiment provides a high-strength refractory ceramic material, which comprises the following raw materials mixed in parts by weight: Industrial α-alumina powder: 75.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 15.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 6.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 4.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm.
[0037] In addition, add 0.5% of the total mass of the above raw materials as a mineralizing agent, aluminum fluoride, which is chemically pure.
[0038] The preparation method of the high-strength refractory ceramic material in this embodiment is the same as that in Example 1.
[0039] Performance testing: The test method was the same as in Example 1. The test results showed that the 2-hour water-based suspension rate of the powder in this example was 94.8%; the flexural strength at room temperature was 14.6 MPa; the flexural strength at 1200℃ was 11.8 MPa; and no macroscopic cracks appeared on the sample surface after 14 thermal shock cycles.
[0040] Example 3:
[0041] This embodiment provides a high-strength refractory ceramic material, which comprises the following raw materials mixed in parts by weight: Industrial α-alumina powder: 68.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 24.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 2.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 6.0 parts, ZrO2 contains 3 mol% Y2O3, D50 is 80 nm.
[0042] In addition, add 2.0% of the total mass of the above raw materials as a mineralizing agent, aluminum fluoride, which is chemically pure.
[0043] The preparation method of the high-strength refractory ceramic material in this embodiment is the same as that in Example 1.
[0044] The testing method was the same as in Example 1. The 2-hour water-based suspension rate of the powder in this example was 96.0%; the flexural strength at room temperature was 15.8 MPa; the flexural strength at 1200℃ was 12.6 MPa; and no macroscopic cracks appeared on the sample surface after 18 thermal shock cycles.
[0045] Comparative Example 1: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 72.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 3.0 parts, MgO content ≥95%, D50 is 5μm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0046] This comparative example does not add yttrium-stabilized zirconia powder, and the amount of industrial α-alumina powder is adjusted to 72.0 parts to make up for the mass parts lost due to the removal of zirconia powder. The composition of other raw materials and preparation methods are the same as in Example 1.
[0047] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 94.3% after 2 hours; the flexural strength at room temperature was 12.5 MPa; the flexural strength at 1200℃ was 9.2 MPa; and macroscopic cracks appeared on the sample surface after 8 cycles of water cooling thermal shock at 1100℃.
[0048] Comparative Example 2: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 73.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; 3Y-Yttrium stabilized zirconia powder: 2.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0049] The difference between this comparative example and Example 1 is that: lightly calcined magnesium oxide powder is not added, and the amount of industrial α-alumina powder is adjusted to 73.0 parts; the composition of other raw materials and the preparation method are the same as in Example 1.
[0050] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 94.0% after 2 hours; the flexural strength at room temperature was 13.0 MPa; the flexural strength at 1200℃ was 9.8 MPa; and macroscopic cracks appeared on the sample surface after 9 cycles of water cooling thermal shock at 1100℃.
[0051] Comparative Example 3: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 70.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 3.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 2.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm.
[0052] This comparative example does not contain aluminum fluoride, and the composition of other raw materials and preparation methods are the same as in Example 1.
[0053] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 93.8% after 2 hours; the flexural strength at room temperature was 12.8 MPa; the flexural strength at 1200℃ was 9.5 MPa; and macroscopic cracks appeared on the sample surface after 10 cycles of water cooling thermal shock at 1100℃.
[0054] Comparative Example 4: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 70.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 3.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 2.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0055] The raw material composition of this comparative example is the same as that of Example 1. The preparation method is as follows: after completing the batching, ball milling and spray granulation according to the method of Example 1, without high-temperature pre-sintering, the spray-granulated particles are directly pulverized by air jet milling and air jet classification to obtain powder with a median particle size D50 of 20 μm; then the powder is placed in a high-speed mixer, and 4% of neutral silica sol with a SiO2 content of 30% is sprayed into it. After coating for 30 min, it is dried at 105℃ for 2 h to obtain the powder.
[0056] The difference between this comparative example and Example 1 is that the spray-granulated particles were not pre-sintered at high temperature, and the mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure was not pre-formed in the powder. Instead, it exists in the form of original oxide raw material particles.
[0057] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 93.5% after 2 hours; the flexural strength at room temperature was 13.8 MPa; the flexural strength at 1200℃ was 10.5 MPa; and macroscopic cracks appeared on the sample surface after 10 cycles of water cooling thermal shock at 1100℃.
[0058] Comparative Example 5: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 70.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 25.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 3.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 2.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0059] The preparation method of this comparative example is as follows: the batching, ball milling, spray granulation, high-temperature sintering at 1500℃, crushing, air jet milling and classification are completed according to the method of Example 1 to obtain a multiphase ceramic powder with a median particle size D50 of 20μm, but without silica sol liquid phase coating treatment.
[0060] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 82.0% after 2 hours; the flexural strength at room temperature was 12.0 MPa; the flexural strength at 1200℃ was 9.0 MPa; and macroscopic cracks appeared on the sample surface after 8 cycles of water cooling thermal shock at 1100℃.
[0061] Comparative Example 6: This comparative example provides a refractory ceramic material, wherein the following raw materials are mixed in parts by weight: Industrial α-alumina powder: 80.0 parts, Al2O3 content ≥99%, median particle size D50 is 3μm; High-purity silicon micro powder: 10.0 parts, SiO2 content ≥98%, D50 is 1μm; Lightly calcined magnesium oxide powder: 5.0 parts, MgO content ≥95%, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 5.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0062] In this comparative example, the amount of industrial α-alumina powder used was 80.0 parts, which was higher than the 70.0 parts used in Example 1, and the amount of high-purity silicon micro powder used was 10.0 parts, which was lower than the 25.0 parts used in Example 1. The rest of the preparation methods were the same as in Example 1.
[0063] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 92.5% after 2 hours; the flexural strength at room temperature was 11.8 MPa; the flexural strength at 1200℃ was 8.6 MPa; and macroscopic cracks appeared on the sample surface after 6 cycles of water cooling thermal shock at 1100℃.
[0064] Comparative Example 7: This comparative example provides a refractory ceramic material, which uses mechanically mixed multiphase aggregate, and the following raw materials are mixed in parts by weight: Mullite powder: 82.0 parts, D50 is 20μm; Fused magnesium aluminum spinel powder: 8.0 parts, D50 is 5μm; 3Y-Yttrium stabilized zirconia powder: 10.0 parts, ZrO2 containing 3 mol% Y2O3, D50 is 80 nm; In addition, 1.0% of the total mass of the above raw materials is aluminum fluoride, which is chemically pure.
[0065] In this comparative example, the mullite powder is commercially available fused mullite powder with an Al2O3 content of 73%, a SiO2 content of 27%, a mullite phase content of 92%, and a median particle size D50 of 20 μm; the fused magnesia-alumina spinel powder is commercially available fused spinel powder with an MgAl2O4 content of 97% and a median particle size D50 of 5 μm. Both powders are conventional commercially available raw materials in the refractory materials field and can be obtained through commercial channels.
[0066] The preparation method of this comparative example is as follows: the above powder is added to a high-speed mixer and dry-mixed for 30 min, then 4% of the total mass of the powder is added to a neutral silica sol with a SiO2 content of 30%, and the mixture is stirred and coated for another 30 min. The powder is then dried at 105℃ for 2 h to obtain the powder.
[0067] The difference between this comparative example and Example 1 is that the multiphase structure was not generated through in-situ solid-phase reaction, but rather the pre-synthesized mullite powder, magnesium aluminum spinel powder and zirconium oxide powder were mechanically mixed.
[0068] After the obtained powder was pressed and sintered according to the method of Example 1, the performance was tested: the water-based suspension rate was 93.0% after 2 hours; the flexural strength at room temperature was 10.2 MPa; the flexural strength at 1200℃ was 7.8 MPa; and macroscopic cracks appeared on the sample surface after 6 cycles of water cooling thermal shock at 1100℃.
[0069] Performance test results:
[0070] From the test results of Examples 1 to 3 and Comparative Examples 1 to 7 above, it can be seen that: Figures 2-4 As shown, the 2-hour water-based suspension rate of the powders obtained in Examples 1 to 3 is ≥94.8%, the room temperature flexural strength is ≥14.6MPa, the high temperature flexural strength at 1200℃ is ≥11.8MPa, and the number of water-cooled thermal shock cycles at 1100℃ is ≥14.
[0071] Compared to Example 1, Comparative Example 1 only lacked the addition of 3Y-yttrium stabilized zirconia powder, and the amount of α-alumina powder was adjusted to 72.0 parts to compensate for the total amount. Due to the lack of dispersed zirconia particles in the sintered body, it was unable to absorb fracture energy during crack propagation through the phase transformation toughening effect of zirconia (t-ZrO2→m-ZrO2 accompanied by volume expansion), nor could it effectively pin grain boundaries to inhibit the growth of mullite and spinel grains. Therefore, its room temperature flexural strength decreased from 15.2 MPa in Example 1 to 12.5 MPa, its high-temperature flexural strength at 1200℃ decreased from 12.1 MPa to 9.2 MPa, and its thermal shock resistance cycle count decreased from ≥15 cycles to 8 cycles. The water-based suspension rate of Comparative Example 1 was 94.3%, indicating that the absence of zirconia powder had little effect on suspension, but deteriorated mechanical properties and thermal shock resistance.
[0072] Compared to Example 1, Comparative Example 2 only omitted the addition of lightly calcined magnesium oxide powder and adjusted the amount of α-alumina powder to 73.0 parts. Due to the absence of MgO, the magnesium-aluminum spinel reinforcing phase could not be generated in situ during high-temperature sintering, resulting in a lack of matching thermal expansion coefficients and grain boundary strengthening effects brought by the spinel phase in the sintered body. Simultaneously, the ability to control grain size decreased. Test results showed that its room-temperature flexural strength was 13.0 MPa, its high-temperature flexural strength at 1200℃ was 9.8 MPa, and its thermal shock resistance was 9 cycles, all significantly lower than the 15.2 MPa, 12.1 MPa, and ≥15 cycles of Example 1, respectively. The suspension rate of this comparative example was 94.0%, similar to Example 1, further indicating that the improvement in suspension was mainly due to silica sol coating, while the decrease in mechanical properties stemmed from the absence of the key reinforcing phase in the multiphase structure.
[0073] Comparative Example 3, compared to Example 1, did not include aluminum fluoride mineralizer. During high-temperature sintering, aluminum fluoride can form a eutectic liquid phase with trace amounts of alkali metal oxides and other impurities in the raw materials, promoting particle rearrangement and mass migration, lowering the mullite phase formation temperature, and increasing sintering density. Without aluminum fluoride, the amount of liquid phase during sintering is insufficient, hindering mass transfer between particles, resulting in decreased sample density and increased porosity, leading to poorer mechanical properties and thermal shock resistance. Its room temperature flexural strength was 12.8 MPa, its high-temperature flexural strength at 1200℃ was 9.5 MPa, and its thermal shock cycle count was 10, all lower than in Example 1. Its suspension rate was 93.8%, which is close to that of Example 1, indicating that the effect of aluminum fluoride is mainly reflected in the sintering process rather than suspension.
[0074] Compared to Example 1, Comparative Example 4 used the same raw material composition, but instead of high-temperature pre-sintering, the spray-granulated particles were directly crushed, graded, and coated with silica sol. Because it did not undergo a solid-phase reaction at 1500°C, the mullite-magnesium aluminum spinel-zirconia multiphase structure was not pre-formed in the powder; instead, it existed as a mixture of original particles of α-Al₂O₃, SiO₂, MgO, and ZrO₂. During subsequent pressing and sintering, although an in-situ reaction could occur again, the reaction temperature and time differed from the pre-sintering process. Furthermore, the powder particles were already coated with silica sol, resulting in a longer diffusion distance of the reactants, leading to incomplete reaction, insufficient formation of the multiphase structure, and low density of the sintered body. Its room-temperature flexural strength was 13.8 MPa, its high-temperature flexural strength at 1200°C was 10.5 MPa, and its thermal shock resistance was 10 cycles, all lower than that of Example 1. Its suspension rate was 93.5%, slightly lower than that of Example 1, indicating that the pre-sintered multiphase powder is more conducive to suspension stability in terms of particle size distribution and surface state.
[0075] Comparative Example 5 and Example 1 had the same raw material composition and high-temperature pre-sintering process, the only difference being the absence of silica sol liquid phase coating. Test results showed that its 2-hour water-based suspension rate was only 82.0%, fully demonstrating that the nano-SiO2 active layer formed by silica sol coating on the powder surface improved the wettability and dispersion stability of the powder in water, and was a key means to obtain high suspension performance. Meanwhile, the powder lacking the coating layer experienced lower flexural strength (12.0 MPa at room temperature, 9.0 MPa at 1200℃, and 8 thermal shock cycles) during subsequent molding and sintering due to the lack of the nano-SiO2 active layer promoting sintering. These results were also lower than in Example 1, indicating that silica sol coating not only determines suspension performance but also synergistically contributes to the mechanical properties of the sintered body.
[0076] Compared to Example 1, Comparative Example 6 increased the amount of α-alumina powder to 80.0 parts and decreased the amount of high-purity silica powder to 10.0 parts. Under this ratio, the amount of mullite generated during pre-sintering decreased, the content of unreacted free α-Al₂O₃ increased, and the phase composition of the sintered body deviated from the target multiphase structure. Simultaneously, the reduced silica powder content led to insufficient high-temperature liquid phase, resulting in a decrease in sintering density. Its room-temperature flexural strength was 11.8 MPa, its high-temperature flexural strength at 1200℃ was 8.6 MPa, and its thermal shock resistance cycle was only 6 times, all of which were inferior to those of Example 1. Its water-based suspension rate was 92.5%, also lower than that of Example 1, indicating that deviating from the multiphase composition ratio simultaneously impairs both powder suspension and the mechanical properties of the sintered body.
[0077] Compared to Example 1, Comparative Example 7 did not employ an in-situ solid-phase reaction route. Instead, it directly used commercially available pre-synthesized mullite powder, fused magnesium aluminum spinel powder, and 3Y-zirconia powder, which were mixed in a specific mass ratio and then coated with silica sol. Because the commercially available multiphase powders have coarse particle sizes and wide particle size distributions, and lack the tight interfacial bonding generated by in-situ reactions between the components, mechanical mixing could not achieve a uniform distribution at the nanometer / micrometer level, resulting in an uneven microstructure and low interfacial bonding strength in the sintered body. Test results showed that its room temperature flexural strength was 10.2 MPa, its high-temperature flexural strength at 1200℃ was 7.8 MPa, and its thermal shock resistance cycle was only 6 times, the lowest among all samples. Its 2-hour water-based suspension rate was 93.0%, also lower than Example 1, indicating that even with silica sol coating, the suspension performance could not reach the level of this invention when the powder particle size and surface characteristics were mismatched.
[0078] In summary, this invention generates a mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure in situ through high-temperature pre-sintering, and utilizes silica sol liquid phase to coat the powder surface to form a nano-silica active layer. At the same time, the raw material ratio, mineralizer addition and multiphase composition must be coordinated to obtain excellent water-based suspension performance, room temperature and high temperature mechanical properties and thermal shock resistance.
[0079] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A high-strength refractory ceramic material, characterized in that, The high-strength refractory ceramic material is a multiphase ceramic powder, which includes multiphase ceramic particles and a nano-silica active layer coating the surface of the multiphase ceramic particles; the multiphase ceramic particles contain mullite phase, magnesium aluminum spinel phase and yttrium-stabilized zirconium oxide phase, and are prepared from the following raw materials by high-temperature pre-sintering in-situ reaction, by mass parts: 68-75 parts of industrial α-alumina powder, wherein the Al2O3 content of the industrial α-alumina powder is ≥99% and the median particle size D50 is 3μm; 15-25 parts of high-purity silicon micro powder, wherein the high-purity silicon micro powder has a SiO2 content ≥98% and a median particle size D50 of 1μm; 2-6 parts of lightly calcined magnesium oxide powder, wherein the MgO content of the lightly calcined magnesium oxide powder is ≥95% and the median particle size D50 is 5μm; 2-6 parts of 3Y-yttrium stabilized zirconium oxide powder, wherein the 3Y-yttrium stabilized zirconium oxide powder is ZrO2 powder containing 3 mol% Y2O3 and the median particle size D50 is 80 nm; The aluminum fluoride is added externally, wherein the aluminum fluoride is chemically pure, and its amount is 0.5% to 2.0% of the total mass of industrial α-alumina powder, high-purity silica powder, lightly calcined magnesia powder, and 3Y-yttrium stabilized zirconium oxide powder; The nano-silica active layer is formed by coating the surface of the composite ceramic particles with neutral silica sol, which accounts for 4% of the total mass of the composite ceramic particles, and then drying it. The SiO2 content in the neutral silica sol is 30%.
2. The high-strength refractory ceramic material according to claim 1, characterized in that: By weight, the industrial α-alumina powder comprises 70 parts, the high-purity silicon micro powder comprises 25 parts, the light-burned magnesium oxide powder comprises 3 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 2 parts, and the amount of aluminum fluoride is 1.0% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
3. The high-strength refractory ceramic material according to claim 1, characterized in that: By weight, the industrial α-alumina powder comprises 75 parts, the high-purity silicon micro powder comprises 15 parts, the light-burned magnesium oxide powder comprises 6 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 4 parts, and the amount of aluminum fluoride is 0.5% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
4. The high-strength refractory ceramic material according to claim 1, characterized in that, By weight, the industrial α-alumina powder comprises 68 parts, the high-purity silicon micro powder comprises 24 parts, the light-burned magnesium oxide powder comprises 2 parts, the 3Y-yttrium stabilized zirconium oxide powder comprises 6 parts, and the amount of aluminum fluoride is 2.0% of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the light-burned magnesium oxide powder, and the 3Y-yttrium stabilized zirconium oxide powder.
5. A method for preparing a high-strength refractory ceramic material suitable for any one of claims 1 to 4, characterized in that, Includes the following steps: S1. By mass, 68-75 parts of industrial α-alumina powder, 15-25 parts of high-purity silicon micro powder, 2-6 parts of lightly calcined magnesia powder, 2-6 parts of 3Y-yttrium stabilized zirconium oxide powder, and 0.5%-2.0% of aluminum fluoride by mass of the total mass of the industrial α-alumina powder, the high-purity silicon micro powder, the lightly calcined magnesia powder, and the 3Y-yttrium stabilized zirconium oxide powder are mixed, and deionized water is added for wet ball milling to obtain a uniform slurry; S2. Spray granulation is performed on the slurry to obtain spherical agglomerated particles; S3. The spherical agglomerated particles are pre-sintered at high temperature, so that alumina reacts in situ with high-purity silicon micro powder to form mullite phase, magnesium oxide reacts in situ with excess alumina to form magnesium aluminum spinel phase, and yttrium-stabilized zirconium oxide is dispersed in the grain boundaries and grain interiors of mullite and spinel to form a mullite-magnesium aluminum spinel-zirconia multiphase ceramic structure. After cooling, the sintered block is subjected to coarse crushing, medium crushing, pulverizing and air classification in sequence to obtain multiphase ceramic particles; S4. The composite ceramic particles are mixed with 4% of the total mass of the composite ceramic particles in a neutral silica sol for liquid phase coating and dried to obtain a high-strength refractory ceramic material; the SiO2 content in the neutral silica sol is 30%.
6. The preparation method according to claim 5, characterized in that: In S1, the mass ratio of material, balls, and water is controlled at 1:2.5:0.8 during wet ball milling, the ball mill speed is 350 r / min, the ball milling and mixing is carried out for 4 hours, and the solid content of the resulting slurry is 55 wt%.
7. The preparation method according to claim 5, characterized in that, In S2, spray granulation is performed using a centrifugal spray drying tower with an inlet air temperature of 190°C, an outlet air temperature of 85°C, and an atomizing disc rotation speed of 12000 r / min. The median particle size D50 of the resulting spherical agglomerated particles is 45 μm.
8. The preparation method according to claim 5, characterized in that, In S3, the pre-sintering process is as follows: heat to 1500°C at a heating rate of 5°C / min, hold at that temperature for 3 hours, and then cool naturally to room temperature.
9. The preparation method according to claim 5, characterized in that: In step S4, the liquid phase coating is carried out in a high-speed mixer for 30 minutes; the drying is carried out at 105°C for 2 hours.
10. The preparation method according to claim 5, characterized in that: In step S3, the coarse crushing is performed using a jaw crusher, the medium crushing is performed using a double roll crusher, the pulverizing is performed using an air jet mill, and the air jet classification is performed using an air jet classifier. The median particle size D50 of the resulting multiphase ceramic particles is 20 μm.
